Psychometric evaluation of the Arthritis Self-Efficacy Scale in Chinese adults with rheumatic diseases: a cross-sectional study. Issue 2 (16th February 2021) - Tsai, Tzung-Yi; Lu, Ming-Chi; Livneh, Hanoch; Lin, Miao-Chiu; Lai, Ning-Sheng; Guo, How-Ran
Abstract : Objective: The Arthritis Self-Efficacy Scale (ASES) was designed to assess the degree of self-efficacy among patients with arthritis. Though the original English version of this instrument has shown a high degree of reliability and validity, a Chinese version of this scale has yet to be validated. Therefore, the aim of this cross-sectional study was to evaluate the psychometric characteristics of the Chinese version of ASES (C-ASES) in a population of Chinese adults with rheumatic diseases (RDs). Methods: After completing backward translation and expert validity, a convenient sample of 258 qualified participants with RDs from a hospital in Taiwan were recruited to explore the content validity, concurrent validity, construct validity, internal consistency reliability and test–retest reliability of C-ASES. Results: The C-ASES has demonstrated acceptable internal consistency and test–retest reliability, with a Cronbach α of 0.91 and intraclass correlation coefﬁcient of 0.89, respectively. Concurrent validity was acceptable, with significant correlation between the subscales of the C-ASES and perceived depressive symptoms, as measured by the Taiwanese Depression Questionnaire (p<0.05). The exploratory factor analysis revealed a three-factor solution (physical function, experienced pain and other symptoms) corresponding to the structure of the original instrument, which accounted for 59.78% of the total variance. Conclusion: Empirical data support the assertion that C-ASES is a reliable and valid screening instrument to assess self-efficacy in Chinese-speaking patients with RDs. C-ASES may be useful as a reference guide in providing appropriate interventions for bolstering self-efficacy among Chinese-speaking patients with RDs.